Ikonisitas dalam Arsip Foto Karya Seni Rupa Dua Dimensional - Patriot Mukmin (JURNAL RUPA, 2021)
Digitalization has brought new complexity to the issue of archival photographs of artworks. This paper explores the relationship between two-dimensional artwork and its representation in the form of digital archive photos. The author mobilizes the concept of the relation between representamens and objects in Charles Sanders Peirce's theory of signs. Based on the analyses carried out in this paper, the presence of the Icon and Index feels very strong in the case of archival photographs of works of art. This finding stresses the need of two types of archival photos of works, namely primary photos and secondary photos. Classification is carried out based on the level of similarity in the representation seen in the archive photo.